2019
DOI: 10.1116/1.5058294
|View full text |Cite
|
Sign up to set email alerts
|

Thermal study of multilayer resistive random access memories based on HfO2 and Al2O3 oxides

Abstract: An in-depth analysis including both simulation and experimental characterization of Resistive RAMs (RRAMs) with dielectric stacks composed of two layers of HfO2 and Al2O3 stacked in different order is presented. The simulator, that includes the electrodes in the simulation domain, solves the 3D heat equation and calculates the device current. The results are employed to analyze thermal effects in bilayer HfO2 and Al2O3-based RRAMs with electrodes of Ni and Si-n+ during resistive switching (RS) operation. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
2
9
0
1
Order By: Relevance
“…The values obtained using Equation () have been compared to those obtained by solving the 3D heat equation (Equation ()) and the current equation for Ag/h‐BN/Au structures. [ 30–31 ] false(kTHfalse(x, y, zfalse)Tfalse(x, y, zfalse)false)+ e˙generatedgoodbreak=0\[ \begin{array}{*{20}{c}}{\nabla ({{\rm{k}}_{TH}}(x,\,y,\,z)\nabla T(x,\,y,\,z)) + \;{{\dot{e}}_{generated}} = 0}\end{array} \] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values obtained using Equation () have been compared to those obtained by solving the 3D heat equation (Equation ()) and the current equation for Ag/h‐BN/Au structures. [ 30–31 ] false(kTHfalse(x, y, zfalse)Tfalse(x, y, zfalse)false)+ e˙generatedgoodbreak=0\[ \begin{array}{*{20}{c}}{\nabla ({{\rm{k}}_{TH}}(x,\,y,\,z)\nabla T(x,\,y,\,z)) + \;{{\dot{e}}_{generated}} = 0}\end{array} \] …”
Section: Resultsmentioning
confidence: 99%
“…The values obtained using Equation ( 1) have been compared to those obtained by solving the 3D heat equation (Equation ( 2)) and the current equation for Ag/h-BN/Au structures. [30][31] (k ( , , ) ( , , )) 0 x y z T x y z e TH generated…”
Section: Temperature Of the Nanofilamentmentioning
confidence: 99%
“…However, XRD temperature experiments of similar films with similar composition have shown that the orthorhombic phase is stable at least up to 1000 C, 51 which is much larger than the evaluated temperature increase in similar devices. 52 Therefore, an intrinsic permittivity decrease related to a phase transformation is unlikely to occur. Alternatively, if the permittivity after the breakdown is fixed to its value before the breakdown, then, assuming the same contact area A, the effective thickness of the capacitor would be increased up to ≈ 7.7 nm.…”
Section: Acs Applied Electronic Materialsmentioning
confidence: 99%
“…As one of the promising candidates for next-generation nonvolatile memories, resistive random access memory (RRAM) has received considerable attention due to significant advantages concerning simplicity of structure, low power consumption, fast read & write speed, high scalability and 3-D integration feasibility compared to the industry standard silicon-based flash memories [1,2,3,4,5,6,7]. Current candidate materials for the resistive switching (RS) layer of RRAM devices include perovskite, ferromagnetic and metal oxide-based materials [1,3,4,5,8,9,10,11]. In particular, metal oxide-based materials such as AlO x , NiO x , TiO x and HfO x are currently extensively discussed because of the simplicity of the material [10,12,13,14].…”
Section: Introductionmentioning
confidence: 99%